‘I Work With my Heart’: Experiences of Migrant Care Workers in a Northern, Rural Context - Munkejord, Mai Camilla (Journal of Population Ageing, 2016)
Submitted manuscript version. Publisher's version available at http://doi.org/10.1007/s12062-016-9157-z . In Norway, long-term care needs are rising rapidly. Due to the dual-earner family model and the fact that many people live far away from frail parents and other dependent family members, the growing care needs may not be met through informal care. Through the Nordic welfare system, formal care services are provided to all citizens in need of care, regardless of their age, income or family relations. Since the 1990s, however, Norway has experienced a shortage of healthcare personnel. In this ‘care deficit’ situation, skilled immigrants play an increasingly important role. To date, the international literature has examined the experiences of the professional migrant care workers in a limited way. In particular, there is a lack of knowledge of this issue in rural contexts where recruitment challenges may be even more pronounced than in urban areas. This article addresses this knowledge gap by examining the spatial and relational experiences of skilled migrants working in the healthcare sector in Finnmark, northernmost Norway. In this study, the informants share largely positive experiences, stating that their care services are highly valued and that caring provides them with a sense of joy and mastery. Moreover, they talk about the importance of establishing trust in the relationship with their users and note that some patients end up becoming almost like family members. The migrants’ relationships with colleagues and management at the workplace are also defined by mainly positive feelings, trust and respect. Caring is hence perceived by the migrants as an inherently sense-making practice .